Treatment With Endothelin-A Receptor Antagonist BQ123 Attenuates Acute Inflammation in Mice Through T-Cell-Dependent Polymorphonuclear Myeloid-Derived Suppressor Cell Activation - Chen, Ziyang; Zhang, Xiaogang; Lv, Shuaijun; Xing, Zhe; Shi, Mengyu; Li, Xinyao; Chen, Meiqi; Zuo, Shaowen; Tao, Yingxu; Xiao, Gang; Liu, Jingping; He, Yumei (Frontiers in Immunology, 2021)
The endothelin-A receptor antagonist BQ123 is an effective treatment agent for hypertension and obese cardiomyopathy. However, the role of BQ123 in controlling acute inflammatory diseases and its underlying mechanisms are not well understood. Here, we showed that BQ123 activated polymorphonuclear myeloid-derived suppressor cells (PMN-MDSCs) in mice and that the IL13/STAT6/Arg1 signaling pathway is involved in this process. Importantly, both treatment with BQ123 and the transfer of BQ123-induced PMN-MDSCs (BQ123-MDSCs) were effective in relieving inflammation, including dextran sulfate sodium (DSS)-induced colitis, papain-induced pneumonia, and concanavalin A (ConA)-induced hepatitis, in mice. The treatment effects were mediated by the attenuation of the inflammation associated with the accumulation of PMN-MDSCs in the colon, lung, and liver. However, concurrent injection of Gr1 agonistic antibody with BQ123 induced PMN-MDSC aggravated the observed acute inflammation. Interestingly, no remission of inflammation was observed in Rag2 knockout mice administered BQ123-MDSCs, but co-injection with CD3+ T cells significantly relieved acute inflammation. In summary, BQ123-induced PMN-MDSCs attenuated acute inflammation in a T cell-dependent manner, providing a novel potential strategy to prevent the occurrence of acute inflammation.